Relevansi Model Pembelajaran Contextual Teaching and Learning terhadap Dinamika Pembelajaran Pendidikan Agama Islam di Era Modern - Gerry Mandala (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the relevance of the contextual learning model in addressing the challenges of monotonous Islamic Religious Education (IRE) instruction in the modern era. Technological advancements and changes in student characteristics demand more active, creative, and meaningful learning innovations. However, PAI instruction in various educational institutions still tends to rely on conventional, teacher-centered methods, leading to student boredom and low engagement in the learning process. This article employs a literature review using a narrative approach to examine the relevance of the contextual learning model in addressing monotonous PAI instruction in the modern era. Data were obtained from 22 scientific journals and analyzed using content analysis to understand the implementation of more active, innovative, and meaningful PAI instruction. The results indicate that the Contextual Teaching and Learning (CTL) approach is a learning model that connects content to real-life situations, thereby making students more active, independent, and capable of critical thinking. In Islamic Education, CTL is relevant for addressing monotonous learning because it helps students understand and practice Islamic values in their daily lives. Although its implementation requires more time and the teacher’s ability to manage the classroom, CTL is capable of creating learning that is more meaningful, innovative, and contextual.